Dental Morphological Affinities Among Late-Pleistocene and Recent Humans - Shara E. Bailey (Dental Anthropology Association, 2000)
The study uses analyses of Mean Measure of Divergence (MMD) to assess the affinities of ten populations representing early anatomically modern humans, Upper Paleolithic Europeans, recent modern humans, and Neandertals. The 18-triat MMD analysis demonstrates that, dentally, Neandertals are quite divergent from all modern humans. The results of cluster analyses based on MMD values suggest two major clusters: Neandertals and modern humans. The data also suggest two sub-clusters within the modern human cluster. One links Upper Paleolithic Europeans with recent North Africans and Europeans. The other links early anatomically modern humans with Late Pleistocene Africans and recent Sub-Saharan Africans. These results do not support a close relationship between Neandertals and any modern human groups samples. They also tentatively suggest that, if the two populations were interbreeding, it is not reflected in their dental morphology. The results showing a close affinity between early anatomically modern humans and Sub-Saharan Africans are consist with the Recent African Origin model for modern human origins.